Evaluation of long-term care insurance pilot city policies in China: a cross-sectional study - Du, Kuan; Liu, Yuan; Hu, Yiran (Frontiers in Public Health, 2025)
BackgroundThe acceleration of China’s aging process makes examining policy experiences from LTCI pilot cities highly significant for advancing the LTCI system in China and other emerging nations.MethodsPolicy documents were gathered using Citespace 6.3.R1, with primary data sources obtained from official government websites. A comparative study of LTCI policies in pilot cities was conducted, focusing on policy support, participation scope, financing channels, benefit provision, care conditions, and management structures to evaluate the programs’ logic.ResultsPilot cities have developed distinct approaches in the LTCI development process. However, issues persist, including a singular financing channel, misalignment between benefit provision supply and demand, substandard care quality, and the need for improved management effectiveness.DiscussionEstablishing a sustainable LTCI system requires implementing an independent financing mechanism and a standardized financial model, developing an efficient LTCI service supply framework, strengthening LTCI oversight and administration, and fostering the commercial insurance market.